Sustainable alternative (Takakura) for the organic waste minimization in the Saltos farm, in the Salitre canton, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2022)
The application of sustainable alternatives, after characterization of the solid waste, has allowed the use of the Takakura method, which consists of sweet and salt solutions in 2.5 liters of water, which is incorporated into the fermentation bed, activating beneficial microorganisms in the composting process. A total of 64 kg of organic waste was decomposed, which represents a 78.43% of decomposition rate after 30 days. The physical-chemical parameters remained constant except for the temperature, which reached a maximum of 56 °C in TI2, and in the TI1 composter, which had the lowest pH value of 8.7. The micronutrients and macronutrients were found within normal ranges, concluding that the composting is a very useful method in the decomposition of organic waste in rural areas that do not have waste collection services.
Keywords: Takakura; Composting; Organic waste